Does the implementation of a moratorium bring positive shock to the bank stock price amidst the global pandemic? - Azmi Majid; Rozilee Asid; Lim, Thien Sang; Zaiton Osman (Penerbit Universiti Malaysia Sabah, 2024)
Malaysia was the only nation that provided moratorium on loan repayment in a blanket basis during the global pandemic. Thus, this study examines the whether moratorium has a contractionary or an expansionary impact from the perspective of loan repayment towards the volatility of banking stock prices listed in Bursa Malaysia. The Exponential GARCH (EGARCH) was employed with daily data from 2 January 2019 to 31 December 2021. The empirical findings showed that the loan-repayment moratorium induced a positive shock to the volatility of Hong Leong Bank, Public Bank, RHB Bank, and Alliance Bank. However, all these banks exhibit a leverage effect, and negative shocks were more pronounced towards their stock price volatility during the moratorium implementation. The findings were crucial for investors and authorities to understand the impact of a moratorium on the banks towards the stock price.